2016
DOI: 10.1111/ejn.13438
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐specific modulation of odorant representations in the honeybee brain

Abstract: Ca imaging techniques were applied to investigate the neuronal behavior of projection neurons in the honeybee antennal lobe (AL) to examine the effects of long-lasting adaptation on odorant coding. Responses to eight test odorants were measured before, during, and after an odor adaptation phase. Bees were exposed to the adapting odor for 30 min. Test odorant responses were only recorded from a sub-population of accessible glomeruli on the AL surface. Projection neurons, the output neurons of the antennal lobes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Recently, Chakroborty et al (2016) reported on changes in PN activity following 30 min adaptation of the olfactory system through exposure to complex mixtures. In our experiments, a long-duration preexposure was used to study the so-far-unaddressed issue of structural plasticity in relation to unrewarded odor exposure, which requires longer timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chakroborty et al (2016) reported on changes in PN activity following 30 min adaptation of the olfactory system through exposure to complex mixtures. In our experiments, a long-duration preexposure was used to study the so-far-unaddressed issue of structural plasticity in relation to unrewarded odor exposure, which requires longer timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Eicosane melts at ∼37°C; well below maximum flight muscle temperature during flight in Calliphora (∼42°C, Stavenga et al, 1993). It is commonly used in insect research (Vallet et al, 1992; Szyszka et al, 2005; Haehnel et al, 2009; Yamagata et al, 2009; Chakroborty et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…1a). This allowed to complement the morphological atlas with the functional response properties of glomeruli in the honeybee antennal lobe (Galizia et al 1999b;Sachse et al 1999) (see also https ://neuro .uni-konst anz.de/honey beeAL atlas ), which has been used to investigate the principles of olfactory coding (Deisig et al 2006;Deisig et al 2010;Paoli et al 2016b;Paoli et al 2018;Sachse and Galizia 2003), the relationship between perceptual and chemical similarity of odorants (Carcaud et al 2012;Guerrieri et al 2005), as well as changes in olfactory representation upon learning (Chakroborty et al 2016;Chen et al 2015;Hourcade et al 2009;Rath et al 2011).…”
Section: Olfactory Sensory Neuronsmentioning
confidence: 99%